Determination of Physical Activity Levels of Taekwondo Coaches - Şükran Arıkan; Yusuf Barsbuğa; Serkan Revan (Selcuk University, 2019)
Abstract The aim of this study is to determine the physical activity levels of taekwondo trainers. The total of 544 (132 women, 412 men) trainers participated in the trainer development seminars organized by Turkey Taekwondo Federation participated as volunteers in this research.The physical activity levels of the participants were determined with the short form of the  International Physical Activity Questionnaire (UFAA). SPSS 22.0 statistical package program was used to evaluate the data obtained within the scope of the research. The data were analyzed by Kolmogorov-Smirnov test for normality. The Mann- Whitney U test was used because the data were not distributed normally and the significance level was accepted as 0.05. According to the research findings, 3.2% of the trainers had low physical activity level, 61.4% had moderate and 35.5% had high physical activity level. There were statistically significant differences in mean age, height and body weight (p lt;0,05), no significant difference was found between male and female trainers in sitting, walking, moderate physical activity, high intensity physical activity and total physical activity scores (p gt; 0.05). It can be said that most of the taekwondo coaches have moderate physical activity levels.